Astrotischeria neotropicana sp. nov.—a leaf-miner on Sida, Malvaceae, currently with the broadest distribution range in the Neotropics (Lepidoptera, Tischeriidae) - Diškus, Arūnas; Stonis, Jonas R. (Zootaxa, 2015)
This paper describes Astrotischeria neotropicana Diškus & Stonis, sp. nov. (Lepidoptera: Tischeriidae), a new leaf-miner on Sida (Malvaceae) with a broad distribution range in tropical Central & South America. The new species is currently recorded from the Amazon Basin in Peru and Ecuador to tropical lowlands in Guatemala and Belize (including the Caribbean Archipelago). The new species is illustrated with photographs of the adults, male and female genitalia, and the leaf-mines; distribution map is also provided.